Aktivitas Antibakteri Ekstrak Daun Akasia (Acacia auriculiformis) terhadap Pertumbuhan Bakteri Bacillus sp., Staphylococcus aureus dan Escherichia coli - Nurul Hidayah; Gaby Maulida Nurdin; Nur Afia Ameliani (Bionature, 2022)
The increasing of bacterial resistance to antibiotics, which encourages the use of herbal medicines in treating infectious diseases. Acacia auriculiformis leaves are known to have metabolites that can act as an antibacterial agent. This study aimed to determine the antibacterial activity of A. auriculiformis leaves extract against the growth of Bacillus sp., Staphylococcus aureus and Escherichia coli bacteria in vitro. This research was conducted by extracting the leaves of A. auriculiformis using ethanol as a solvent. The inhibition test of A. auriculiformis leaf extract was carried out using the well diffusion method. Antibacterial activity was indicated by the presence of a clear zone around the well. The results showed that the leaf extract of A. auriculiformis had the ability to inhibit the growth of Bacillus sp. and Staphylococcus aureus with the category of strong inhibition. Leaf extract of A. auriculiformis was not able to inhibit the growth of Escherichia coli. Phytochemicals screening test showed that A. auriculiformis leaf contains flavonoids and tannins compounds as antibacterial. Therefore, A. auriculiformis leaves extract had the ability to inhibit the growth of Gram positive bacteria but not Gram negative bacteria.